suPAR as a marker of infection in acute kidney injury – a prospective observational study - Anna Hall; Siobhan Crichton; Matt Varrier; Danielle E. Bear; Marlies Ostermann (BMC Nephrology, 2018)
Abstract Background Soluble urokinase-type plasminogen activator receptor (suPAR) has emerged as a new sepsis biomarker. It is not known whether suPAR has a role in critically ill patients with severe acute kidney injury (AKI). Methods Our main aims were to describe serial serum suPAR concentrations in patients with severe AKI, to investigate a potential association between suPAR and C-reactive protein (CRP), and to compare suPAR and CRP as diagnostic markers of infection in patients with AKI. Between April 2013 – April 2014, we recruited adult patients (≥18 years) with AKI KDIGO stage 2/3 admitted to a multidisciplinary Intensive Care Unit (ICU) in a University Hospital in UK. Serial serum suPAR and CRP concentrations were measured for 6 days. We compared the characteristics and serial suPAR and CRP concentrations of patients with and without an infection using Chi-squared, Fisher’s exact, t-test and Mann-Whitney tests as appropriate, and calculated the area under the receiver operating characteristics curve (AUC). Results Data of 55 patients with AKI stage 2/3 were analysed (62% male; mean age 60.5) of whom 43 patients received continuous renal replacement therapy. suPAR was not detectable in effluent fluid. There was no significant correlation between daily suPAR and CRP concentrations. In patients with an infection, suPAR results were significantly higher than in those without an infection across all time points; there was no significant difference in CRP levels between both groups. After exclusion of patients with an infection before or on day of admission to ICU, the AUC of suPAR for predicting an infection later was 0.62 (95% CI 0.43–0.80) compared to 0.50 (95% CI 0.29–0.71) for CRP. Conclusions In critically ill patients with AKI stage 2/3, suPAR is a better marker of infection than CRP. Trial registration The study was retrospectively registered on the ISRCTN registry on 25 November 2012 (ISRCTN88354940).